Marked Retroperitoneal Lymphadenopathy in Hairy Cell Leukemia: A Case Report - R.E. Shackelford (Case Reports in Oncology, 2013)
Hairy cell leukemia (HCL) is uncommonly associated with lymphadenopathy, while retroperitoneal lymphadenopathy is extremely uncommon. We report on a patient with a 12-year history of HCL who developed painless jaundice and ascites, accompanied by positional discomfort with persistent nausea. Computed tomography examination revealed 2 large retroperitoneal masses, which at autopsy consisted of HCL with focally intermixed pancreatic and peripancreatic tissue. Lymphadenopathy was not identified above the diaphragm or below the aortic bifurcation. No vasculitis or an unusual HCL histology was identified. As previous reports, our findings suggest that HCL with massive lymphadenopathy has a specific site predilection, but it is not necessarily accompanied by vasculitis or an unusual histology.